The 8–11th c. Curonian Men and Women Ornamental Fashions – World Models - Bliujienė, Audronė (Archaeologia Lituana, 1999)
In the 8th–11th c. Curonian men and women used to wear various bronze adornments. Some were common for both men and women, others were preferred by either men or women. Such adornments as cross-bow brooches with animal heads, cross-bow brooches with poppy heads and so-called owl brooches were worn only by men whereas round pendants of various shapes, pins for fastening head-dresses, cross-bow brooches with rings on the shaft, pins with cross-shaped heads were strictly female. The adornments mentioned above denote not only sex, but also features of Curonian worldview based on the concept of the four-part (horizontal) space of the World Tree (WT). The idea is that these adornments were models of the four-part (or eight-part) world space (though in this article adornments based only on the four-part space of WT are being discussed). Thus some adornments mentioned above served as perfect amulets: cross-bow brooches with animal he ails, cross-bow brooches with poppy heads and owl brooches (male adornments), round pendants (female adornments). Investigators of mythology say that the old Baltic culture was formed according to the world model expressed by WT principle. WT idea is reflected in oral folklore, cloth design, national outfit, decoration of various tools and dowry chests. Since the world model expressed in WT shape has been so obviously perpetuated in the ethnographic material, it must have been retained in the archaeological finds as well, including adornment shape, ornamentation, way of wearing, etc. Geometric motifs earlier used in Neolithic ceramics, wooden handicraft wares, amber adornments, were developed and adjusted to bronze and silver adornments. In the late 15th–16th c., when metal adornments ceased to be worn, most of the geometric motifs were transferred to wooden handicraft wares, cloth and ceramics design. The image of WT, which was formed in the late Neolithic era and perpetuated quite obviously in the bronze age, is an all-embracing and all-explaining image of the world concept (fig. 1: 1). The vertical (three-part) structure of WT connects Heaven, Earth and Underground World. In the shape and ornamentation of 8th–11th c. Curonian adornments the vertical structure of WT is much less obvious than the horizontal one. The horizontal structure circumscribes the space around WT, connects people and various objects on both sides of WT. The horizontal WT structure consists of four parts. Such kind of structure enabled one to find one’s bearings in space – to have certain starting points: the North – the South, the East – the West. Thus the world model protected people from four main sides and due to space movement and flow of time from four additional directions: the north-west, the north-east, the south-east and the south-west. Through the form and ornamentation of adornments people at the same time created their world models (fig. 1:1–2; 2–6). Therefore the form, construction and ornamentation of those adornments began to include figures 4 and 8. Thus the world model created an absolutely secure space for people’s living: cultivated land was protected from all possible directions, and the world of the dead was safely separated from that of the living. Due to three-part and four-part space of WT people were able to create their counting systems – triple and quadruple. The WT four-part space was based on the quadruple system. Therefore the Curonians’ preference of figures 4 and 8 is quite comprehensible. These figures are reflected in the shape, construction and ornamentation of adornments (number of motifs, grouping of motifs). Figures 4 and 8 expressing the four-part or the eight-part space are best understood and explained by dividing a circle into 4 or 8 parts. The circle, as an imaginary world space, is divided into four parts by two intercrossing lines. Dividing the circle into 8 parts includes additional directions mentioned above. When trying to go deeper into the semantics of the Baltic geometric ornament, adornment shape and construction, one can find features which are determined and stimulated by the worldview and its corner-stone – the WT with its three part (vertical) and four-part (horizontal) space. If an adornment is decorated according to the three-part space model, the dominating figures in its construction and ornament system will be 3, 6, 9. When the four-part system is the basis, figures 4, 8, 16 will be dominating. These different WT spaces are never confused unless adornment decoration contains production errors (fig. 4). The tree-part and four-part WT spaces are characterised by the sum 3 + 4 = 7. In this way the WT is expressed in a hollow pendant from Stagnai (Klaipėda region) burial ground (fig. 5). The vertical structure of this pendant is clearly three-part whereas the horizontal structure is four-part. The ornamentation of the pendant also includes figure 12, which characterises the existence of the circumscribed space for one year. In somewhat different way the year is defined in a 3rd–4th c. hollow brooch from Pryšmančiai burial ground (fig. 6), in which it is related only to the four-part space. Circumscribing of vertical (Heaven, Earth, Underground World) and horizontal (the North – the South, the East – the West) spaces of the WT, it is not only the philosophical system that is created, but also a certain cultural field, in which gods can create, people can live, animals can exist, plants can grow, i.e. such a field, where every pebble has a clearly perceived purpose and a clearly defined place. The shape, construction and ornamentation of Curonian male and female adornments mentioned above correspond to the WT horizontal four – part space model. It is the four-part (eight-part) WT space that was most relevant for 8th–11th c. Curonians, who were active history creators on the Eastern Baltic coast. The transition of four-part (eight-part) space from the “equilateral cross in a circle” Composition into “imaginary cross in a diamond” (a pin with a prolonged diamond-shaped head), “imaginary cross” (pins with flat hollow heads) or “equilateral cross” constructions due to adornment construction (cross-bow brooches) or shape (cross-bow pins) is quite logical. In the adornments mentioned above, as far as their shape and construction allows, a four-part world model is emphasised. The protection provided by this world model was needed both by men and women, but the adornments of the two genders perpetuated the four-part space in different ways. In the male (warrior) world of the 8th–11th c. the adornments used to be more dynamic than the female ones, with more external influence. In male adornments features of zoomorphic style are clearly expressed. Female adornments-world models have retained traditions of geometric ornamentation and tranquillity of ornaments for a longer period of time. Nevertheless, all these different male and female adornments were decorated with similar elements of geometric ornament (table 1–2). Male adornments. Cross-bow brooches with animal heads of the 8th–9th c. have been found in Lamata Land, where Curonians used to live (present territory of Lithuania and Latvia). Several brooches of this type were also found in the former areas of Žiemgaliai. Besides, cross-bow brooches with animal heads are known to be found in the former Prussian territory. According to the data of 1978, only in Lithuania more than 80 brooches were found in 11 archaeological sites. Cross-how brooches with animal heads are divided into 2 types. Brooches of the first type end with realistic reptile limbs (fig. 7:1; 8–9). Brooches of I a subtype are worth mentioning. Brooches of the second type have a trapezium-shaped plate on the spiral (fig. 7:2–6). Brooches of the II a subtype are of special interest – they are transitional brooches between crossbow brooches with animal heads and cross-bow brooches with poppy heads (fig. 10). Cross-bow brooches with poppy heads are found in the graves of the 8th–11th c. This is one of the last type of crossbow brooches worn by the Balts. Maybe for this reason in the style and ornamentation of these brooches certain degradation can be felt. Cross-bow brooches with poppy heads are found in the former areas of Curonians, Latgaliai, Skalviai, Lamatiečiai, Žemgaliai and Samogitians. Cross-bow brooches with poppy heads can be divided into 2 types. Brooches of the first type are found in the 8th–9th c. graves and have many features of zoomorphic (animal) style (fig. 11–13). Brooches of the second type are found in 10th–11th c. graves and portray totally abstract reptiles (fig. 14–15). Brooches reminding an owl head with open eyes (owl brooches) are found in the late 6th–9th century graves of rich Curonians, Latgalians, Žiemgaliai. These brooches are characteristic only of well-armed men’s graves (fig. 16). Owl brooches have originated from similar brooches that were widely spread in Gotland in the 5th c. But in the late 6th–9th c. these brooches were produced, developed, improved and applied to the Baltic worldview in Lithuania and Latvia. The oldest owl brooches found in the former Curonian areas are dated hack to the 7th – early 8th c. Owl brooches were adjusted by Curonian and Latgalian jewellers to the cross-bow brooch types prevailing in the Baltic areas. Summing up all the information on the 8th–11th c. male adornments, one can conclude that male adornments were more influenced by the Scandinavian world than the female ones. The Scandinavians brought various realistic animal motifs that were later used in traditional Baltic adornments, namely cross-bow brooches and other adornments. Within the Baltic shape, construction and environment, animal motifs were also applied to the Baltic worldview, which had been formed according to the principle of the World Tree model. From the alien aggressive and curling animal motifs only the very abstract idea of motion and visually realistic animal was derived (abstract geometric moving animal motifs in the Baltic worldview were known earlier) and adjusted to the Baltic wordview. Female adornments. Round pendants are the most interesting adornments-amulets most Closely related to the four-part WT space. They are found in the area of a dead woman’s waist, usually on the left side. Round pendants can be divided into two types. Pendants of both types are covered with a hammered silver plate. The main motif of ornamentation is the equilateral cross (fig. 1:2; 17). The head shape and ornamentation of the round pins corresponds to the concept of four-part WT space. Here the equilateral cross is composed into a circle (circles) or a diamond. Some pin-heads contain an obvious equilateral cross (fig. 18–1:3), others contain an imaginary one. According to 1978 data, only 7 pins with stretched diamond-shaped heads are found – in Gudeliai, Laiviai and Palanga burial grounds. Pins of this type are of special interest as their diamond plane, similarly as the circle, can be used for expressing the concept of four-part WT space. The imaginary equilateral cross is emphasised on the corners of the diamond head (fig. 18:5). In the 10th–11th c. burial grounds of north-western Lithuania pins with flat hollow heads are found. Pins of this type are late Curonian pins used for fastening a head-dress. Their style reflects greater abstraction of four-part world model, which manifests itself in style degradation much like in 10th–11th c. male adornments (cross-bow breaches with poppy heads of the second type). The pins are provided with additional details and ornament motifs (fig. 18:6, 9). Together with pins with flat hollow heads smaller pins were sometimes found, whose head fastening resembles a nail, the head is carved or resembles a snowflake (fig. 18:7–8). Cross-bow brooches with rings are adornments characteristic of Baltic tribes. These are most beautiful Baltic adornments worn from the 3rd–4th c. until late 8th c. or even 9th–11th c. Late 8th–9th c. Curonian brooches belong to the third group (fig. 19–21). Curonian women usually used cross-bow brooches with rings for fastening their head-dresses. Similarly to other types of cross-bow brooches, the shape of cross-bow brooches with rings constitutes an imaginary equilateral cross. The cross is decorated with 8 blossoms (4 blossoms on the stem and 4 on the leg). Cross-pins are adornments most characteristic of Lithuanian and Latvian tribes worn from the late 1st millennium and early 2nd millennium AD. These are pins with their heads shaped as an equilateral cross. Cross-pins, like all other kinds of adornments mentioned here, perfectly express the concept of the WT four-part space. Curonian women used to wear pins of all types, but those of 2–4 types were their favourite. Cross-pins of 2–4 types are found only in former Curonian areas (fig. 22–24). Curonian men and women used to wear different adornments of some types. Nevertheless, the decoration of those adornments did not differ a lost since it was based on Baltic geometric ornaments. Both-male and female adornments were ornamented with the same primary geometric motifs (dots, notches, circles, triangles, etc.) (table 1–2). Nonetheless, there was some diversity in the ornamentation of white metal plates covering bronze adornments. Decoration of female white metal plates is more complex and more various. In the 10th–11th c. the world model based on the four-part (eight-part) World “free space and used in the bronze adornments mentioned above loses its importance in the Curonian worldview. In the late 11th c. production and wearing of adornments based on these worldview principles ceased entirely.